Answer:
Solving the expression we get:
Step-by-step explanation:
We need to solve the expression:
This is a quadratic expression and it can be solved using quadratic formula
Solving:
we can write it as:
The quadratic formula is:
where a = 3, b = -2 and c= 1
Putting values and solving:
So, solving the expression we get:
Answer:
t = 6
Step-by-step explanation:
Because you need to transfer the 64 to the other side dividing and the operation will be t = 384 / 64
Answer:
-3.66
Step-by-step explanation:
6x-3=-25
6x=-22
X=-3.66